The role of sustainable land management for climate change adaptation and mitigation in Sub-Saharan Africa - Pender, John L.; Ringler, Claudia; Magalhaes, Marilia; Place, Frank (TerrAfrica, 2009)
Climate change and land degradation are major threats to the survival and livelihoods of millions of people in Sub-Saharan Africa (SSA). Major new opportunities exist to help improve the livelihoods of African smallholder farmers, pastoralists, and other resource users while mitigating emissions of greenhouse gases, reducing land degradation, and addressing other environmental problems in the context of the current negotiations to develop a post-Kyoto climate change framework, and international, national, and local efforts to promote sustainable land management (SLM) and conserve biodiversity. This issue paper is an executive summary of a larger document with the same title. It seeks to help address these threats and achieve the potential of these opportunities by informing policy makers, development practitioners, and others concerned about these issues about the linkages between climate change and SLM, the opportunities and constraints to promoting climate change mitigation and adaptation through SLM, and the policy and institutional options to overcome theconstraints and realize the opportunities that are now or are becoming available.